Evaluation of Cup Disc Ratio and RNFL Thickness Based on Goldmann Visual Field Test - Tatang Talka Gani; Retno Ekantini; Hartono Hartono; Krisna Dwi Purnomo Jati (Majalah Oftalmologi Indonesia, 2022)
Introduction and Objective : To assess the relationship between the cup-disc ratio of the optic nerve head and peripapilarry RNFL thickness to the visual field loss in glaucoma patients. Methods : Visual field from Goldmann kinetic perimerty and Ocular Computed Tomography (OCT) records from Yap Eye Hospital, Yogyakarta are used to examine the figure of visual field loss in glaucoma patient. Result: Broad spectrum of glaucoma-related visual field defects were observed from 73 eyes. The most common visual field defects are arcuate defect (23.3%) and followed by general depression. Arcuate defects can already observable in some patients with cup-disk ratio of 0.5 (30%).Arcuate defect occurs in the average RNFL thickness of 69.90 ?m (46.93-118.77). It appears that the pinhole vision appeared on the average RNFL thickness of 44.23 ?m (25.33-63.13), and temporal RNFL thickness remnant occured at 48.64 ?m (46.22-51.06). RNFL thickness with normal visual field was on the thickness of 107.78 ?m (100.27-115.29). Conclusion: Visual field defect that may be observed in glaucoma with Goldmann kinetic perimetry are arcuate defect, and general visual field depression. RNFL thickness may be correlated longitudinally with the worsening of visual field defect.